Gender-Based Mass Shootings: An Examination of Attacks Motivated by Grievances Against Women - Silva, Jason R. (Violence against women, 2021)
This study provides a quantitative examination of gender-based mass shootings in America from 1966–2018. Gender-based mass shootings refer to attacks motivated by grievances against women, divided into four categories based on a specific woman or women in general, as well as whether they directly target the source of their grievances. Findings indicate that specific woman–targeted shooters were the most common and significantly different from their counterparts in their domestic violence history, racial diversity, and engagement in spree attacks. When comparing all gender-based attacks against other mass shootings, significant differences include relationship status, children, domestic violence history, substance abuse history, and suicide. This investigation provides implications for gender and mass shooting scholars, as well as practitioners developing strategies for intervention and prevention.